A comparative study on ratcheting deformation between negative Poisson's ratio electrode and thin film electrode in Li-ion battery cyclic operation. (November 2020) - Weng, Li; Xu, Chengjun; Chen, Bingbing; Zhou, Jianqiu; Cai, Rui; Shi, Yutao
Abstract: In the charging/discharging cycle of battery, electrode may expand/shrink cyclically and be in an asymmetric behavior of tension and compression. Based on this, electrode may undergo elastic deformation and inelastic deformation, which can naturally result in the electrode ratcheting deformation and capacity fading. In this paper, a new analytical model is developed to study the ratcheting deformation of thin film electrode and negative Poisson's ratio electrode (hollow re-entrant honeycomb shape) in battery cyclic operation. The influence of concentration-dependent material properties on electrode ratcheting deformation is discussed in detail. By the comparison between thin film electrode and negative Poisson's ratio electrode, it is found that the stress level in negative Poisson's ratio electrode is relatively low due to the faster appearance of the inelastic deformation. Furthermore, the structure optimization of negative Poisson's ratio electrode can suppress the ratcheting deformation (produce less accumulated deformation) in battery operating cycles and increase the battery cycle life about 8.1% when compared with thin film electrode. Our work shows that the electrode mechanical degradation is in the form of ratcheting deformation when subjected to cyclic loading. The developed analytical model of negative Poisson's ratio electrode may help for the electrode design and provide a theoretical way to prolong the cycle life of the battery. Highlights: The electrode ratcheting deformation mechanism under cyclic loading is obtained. Electrode mechanical degradation is in ratcheting form under battery operation. Negative Poisson's ratio structure can suppress electrode ratcheting deformation. The concentration-dependent property effect on ratcheting deformation is studied.